The MIMIC Study: Prognostic Role and Cutoff Definition of Monocyte‐to‐Lymphocyte Ratio and Lactate Dehydrogenase Levels in Metastatic Colorectal Cancer. (23rd March 2020) - Basile, Debora; Garattini, Silvio Ken; Corvaja, Carla; Montico, Marcella; Cortiula, Francesco; Pelizzari, Giacomo; Gerratana, Lorenzo; Audisio, Marco; Lisanti, Camilla; Fanotto, Valentina; Ongaro, Elena; Iacono, Donatella; et al.
Abstract: Background: Monocyte‐to‐lymphocyte ratio (MLR) and lactate dehydrogenase (LDH) levels are circulating biomarkers that provide information about tumor‐related inflammation and immune suppression. This study aimed to evaluate the prognostic role of MLR and LDH in metastatic colorectal cancer (mCRC). Material and Methods: This multicentric study analyzed a consecutive cohort of 528 patients with mCRC treated in 2009–2017. The whole population was randomly divided in training and validation cohort. The first was used to identify a threshold for MLR and to create the prognostic model with MLR and MLR‐LDH combined (group 1: MLR‐LDH low; group 2: MLR or LDH high; group 3: MLR‐LDH high). The second cohort was used to validate the model. Results: At the median follow‐up of 55 months, median overall survival (OS) was 22 months. By multivariate analysis, high MLR >0.49 (hazard ratio [HR], 2.37; 95% confidence interval [C.I.], 1.39–4.04), high LDH (HR, 1.73; 95% C.I., 1.03–2.90) in the first model, group 2 (HR, 2.74; 95% C.I.; 1.62–4.66), and group 3 (HR, 3.73; 95% C.I., 1.94–7.18) in the combined model, had a worse prognosis in terms of OS. These data were confirmed both in the validation set and then in the whole cohort. Conclusion: MLR and LDH are circulating cost‐effective biomarkers, readily available in clinical practice, that can be useful for predicting the prognosis of patients with mCRC. Implications for Practice: High monocyte‐to‐lymphocyte ratio (MLR) and lactate dehydrogenase (LDH) levels could be a sign of a tumor's recruitment of suppressive and inflammatory cells worsening prognosis of different types of cancer, including colorectal cancer (CRC). Currently, no data are available for metastatic CRC regarding a cutoff definition for MLR or the prognostic impact of MLR and MLR‐LDH combined. The present study showed in the training cohort and confirmed in the validation and whole cohort that MLR is a reliable and independent laboratory biomarker, which is easy to use, to predict clinical outcomes in patients with mCRC. Moreover, MLR and composite MLR‐LDH could potentially result in an incremental improvement in the prognostic value of these biomarkers, being used as stratification tools for patients with mCRC. Abstract : Evidence suggests a pivotal role of the crosstalk between tumor microenvironment and the immune system that may be a hallmark of spreading cancer. This article evaluates the prognostic role of monocyte‐to‐lymphocyte ratio and levels of lactate dehydrogenase in patients with metastatic colorectal cancer.